Novel loop structure of human IgG1 Fc fused CD38 targeted bispecific antibodies and their anti-tumor effect in acute myeloid leukemia - Shisen Wang; Manling Chen; Tong Zhou; Chengcai Guo; Zhifeng Yan; Yingxi Xu; Haiyan Xing; Kejing Tang; Zheng Tian; Qing Rao; Shaowei Qiu; Ying Wang; et al. (Journal of Translational Medicine)
Abstract Background Acute myeloid leukemia (AML) still lacks an ideal immunotherapy target. CD38 serves as a potential therapeutic target for AML. Classical bispecific antibody (BsAb) requires continuous infusion due to small molecular size and short half-life. Methods The anti-human CD38 single-chain variable fragment (scFv) and anti-human CD3 scFv were cloned to expression plasmids. ExpiCHO-S cells were transfected, and the anti-CD38/anti-CD3 bispecific antibody (38-3-BsAbs) in CHO supernatants was efficiently purified. The anti-AML efficacy of 38-3-BsAbs was evaluated in vitro and in vivo. Results The novel loop structures of non-human IgG Fc fused and human IgG1 Fc fused anti-CD38/anti-CD3 BsAbs, 38-3-loop-BsAb and 38-3-loopFc-BsAb, were designed and produced. Both 38-3-loop-BsAb and 38-3-loopFc-BsAb showed excellent anti-AML effects at low concentrations in vitro. AML xenograft NOD-scid IL2gammanull (NSG) mouse model was adopted to evaluate therapeutic effects of 38-3-BsAb. The anti-leukemic effect of 38-3-loopFc-BsAb was superior. Conclusions We report on new structures of 38-3 bispecific antibody and demonstrate their anti-tumor effect in the treatment of AML.